Correction: Erev, I. et al. a choice prediction competition for market entry games : an introduction - Ion Juvina; Ido Erev; Eyal Ert; Alvin E. Roth (Games, 2010)
Ion Juvina found an error in our manuscript published in Games.
Keywords: 330; epistemic game theory; backward induction; forward induction; algorithms